First evaluation of the practicability of the CLASSYFARM welfare assessment protocol in Italian small-scale mountain dairy farms - a case study - Louis Holighaus; Thomas Zanon; Nicole Kemper; Matthias Gauly (Italian Journal of Animal Science)
The challenges facing the health sector and the agri-food industry have become increasingly complex over the years. Animal welfare, drug consumption, the use of the slaughterhouse as an epidemiological observatory and biosecurity, as well as the health risks associated with it, are increasingly interconnected, making an integrated approach necessary. Hence the European Commission developed regulations to ensure a certain standard for animal welfare in livestock husbandry, which led the Animal Health and Veterinary Drugs Directorate of the Italian Ministry of Health to design an integrated system called Classyfarm, aimed at categorising farming according to risk. The aim of our study was to consider the protocol of the Classyfarm system for evaluating the present situation in South Tyrolean dairy farming (1) and discuss the practical implementation of this new system in small-scale mountain dairy farming (2) which largely differs from large dairy enterprises in the lowlands. The results provide important insights about farm structure and management. However, in terms of animal welfare the questionnaire of Classyfarm is not able to properly differentiate and therefore results need to be considered with caution. Similarly, the section about biosafety is hardly applicable for small-scale mountain farms due to limited herd size and building capacity. Therefore, authors underline the necessity of developing a further differentiated questionnaire for the Classyfarm system, which considers the peculiarities of small-scale mountain dairy farming and allow proper conclusions regarding sanitary risk for public health unless the long-term aim is that such structure will stop producing which will have significant effects on many other sectors in the region, e.g. tourism.